Tracer Gas Test and CFD Analysis of Semiconductor Gas Box for Flammable Gas Leakage - Kim, Shin Eui; Lee, Kwangho; Kang, Chankyu; Jung, Seungho (Energies, 2022)
Semiconductor manufacturing is performed through unit processes that use various chemicals and facilities. In particular, flammable gases, such as H2, NH3, and CH4, are used, and there is a risk of explosion when such gases leak. In this study, computational fluid dynamics (CFD) simulation and a “tracer gas test” according to the SEMI (Semiconductor Equipment and Materials International) S6 Environmental, Health, and Safety Guideline for Exhaust Ventilation of Semiconductor Manufacturing Equipment specification were performed during the leakage of hydrogen, a highly flammable gas used in the etching process of a gas box in the semiconductor industry. The CFD simulation was conducted to investigate the safety of semiconductor production facilities in relation to the explosion risk. Flow analysis was performed for the interior of a gas box used in the etching process. A steady-state analysis was performed to predict the concentration range of the explosion limit in the case of continuous hydrogen gas leakage. The interior of the gas box used in the simulation was modeled, and the ventilation flow rate, which has a significant impact on the leakage gas concentration distribution, obtained from experiments was used. The lower flammability limit (LFL) value of the leaked gas was 4% based on H2, and LFL/4 (25% of the LFL) was analyzed as the explosion limit concentration according to the acceptance criteria of the SEMI S6 tracer gas test. To validate the CFD simulation, a tracer gas test was performed according to SEMI S6. A mixture of hydrogen (5%) and nitrogen (95%) was used as the tracer gas. The flow rate was controlled by a gas regulator valve and measured using an Aalborg mass flow meter. The measured concentration of the tracer gas was calculated using the equivalent release concentration, which was calculated when 100% of the hydrogen was released, and the risk was assessed by comparing it with the LFL/4 of H2.
Keywords: Computational fluid dynamics simulations; Flammable gas; Gas cabinets; Gas leakages; Hydrogen explosion; Lower flammability limits; Semiconductor equipment and materials internationals; Semiconductor industry; Semiconductor manufacturing; Tracer gas; CFD; gas cabinet; hydrogen explosion; semiconductor industry